Portraits of passing time - Teo, Hsin Wei (2019)
Portraits of Passing Time is a series of paintings depicting anonymous people in public spaces performing mundane daily tasks. I find these experiences of “people-watching” somewhat melancholic -- yet there is something about the transience of these moments that I find beautiful. I am struck by the tension in the nostalgia of passing beauty, it spells the imminent detachment from life that living moments have, as time flows relentlessly by. Small moments that fill our daily life seem to be more ephemeral than before. My portraits represent these moments, and in doing so, lead us to empathize with the silent dignity of Passing Time, that often goes by unappreciated.